2015
DOI: 10.5811/westjem.2015.9.27348
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of Predictive Factors for Clinical Deterioration after Admission in Emergency Department Patients Presenting with Abnormal Vital Signs Without Shock

Abstract: IntroductionStrategies to identify high-risk emergency department (ED) patients often use markedly abnormal vital signs and serum lactate levels. Risk stratifying such patients without using the presence of shock is challenging. The objective of the study is to identify independent predictors of in-hospital adverse outcomes in ED patients with abnormal vital signs or lactate levels, but who are not in shock.MethodsWe performed a prospective observational study of patients with abnormal vital signs or lactate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Prior studies have established the clinical utility of using lactate concentration in patients with a variety of critical illnesses [ 2 , 5 , 6 , 11 14 , 19 ]. For instance, Shapiro et al showed that in ED patients with infection, the 28-day in hospital mortality rate was 28% if a single lactate was > 4 mmol/L, 9% if it was 2.5 to 4, and 4.9% if lactate levels were normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have established the clinical utility of using lactate concentration in patients with a variety of critical illnesses [ 2 , 5 , 6 , 11 14 , 19 ]. For instance, Shapiro et al showed that in ED patients with infection, the 28-day in hospital mortality rate was 28% if a single lactate was > 4 mmol/L, 9% if it was 2.5 to 4, and 4.9% if lactate levels were normal.…”
Section: Discussionmentioning
confidence: 99%
“…We enrolled patients with AVS to target an “at risk” population. 19 Patients were enrolled from November 11, 2012, to January 31, 2013. The study was conducted at an urban, academic, tertiary care hospital with 55,000 annual ED visits.…”
Section: Methodsmentioning
confidence: 99%
“…This can have serious implications for patient outcomes. Strategies to ensure good CCDS system usability include incorporating human factor design elements, integrating CCDS system sepsis workflows into current medical emergency clinical pathways, and linking CCDS systems with existing clinical deterioration policies [ 42 , 178 - 180 ]. Only 11.3% (14/124) of the studies we investigated included usability outcomes, with only 14% (2/14) of these studies [ 70 , 93 ] evaluating alert fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a need to incorporate additional factors in any predictive algorithm. Age, serum bicarbonate, and lactic acid have separately been shown to be associated with inpatient deterioration 11…”
Section: Discussionmentioning
confidence: 99%